Cllinical and laboratory profiles of blood donors with erythrocytosis - Kamaruzzaman, Siti Fatimah Mohamed (2016)
In blood banking setting, every blood donors are mandatory to have their haemoglobin (Hb) values tested before blood donation procedure. In current practice, donors with high Hb will be deferred from blood donation. Little attention is given to blood donors with high Hb although is it known that high Hb may indicate an underlying hidden pathological condition. Therefore, the aim of this study is to evaluate the possible underlying aetiologies associated with erythrocytosis in blood donors. A pilot cross sectional study was conducted in Hospital Sultanah Aminah Johor Bahru (HSAJB) and Hospital Universiti Sains Malaysia Kubang Kerian (HUSM) over nine-month period involving blood donors with high pre-donation Hb. A total of 175 samples were collected and analysed for haematological tests, Hb analysis, serum ferritin, biochemical tests and molecular study for the detection of JAK2 V617F mutation. All of the data were analysed using SPSS software version 23.0. The prevalence of blood donors with erythrocytosis was 7.8% (n=175). Among 175 donors, 103 donors were found to have relative erythrocytosis, which mostly contributed by contraction of plasma volume possibly due to dehydration. Another seventy-two (72) donors had absolute erythrocytosis. A total of forty-nine (49) donors had background history of chronic cigarette smoking. We found that there were associations between smoking and thalassaemia/ haemoglobinopathy with erythrocytosis in blood donors. We also found positive correlation between the numbers of blood donation with the degree of erythrocytosis (r = 0.201). The higher the number of blood donations, the higher Hb level will be observed. In conclusion, high Hb in blood donors does indicate hidden pathological aetiology. Quite a number of donors were found to have other significant medical conditions such as thalassaemia/haemoglobinopathy and iron deficiency state. We also strongly suggest that blood donors with high Hb level should be investigated thoroughly in order to exclude any significant pathological conditions that are associated with erythrocytosis.